Quinoa starch granules: a candidate for stabilising food-grade Pickering emulsions - Rayner, Marilyn; Timgren, Anna; Sjöö, Malin; Dejmek, Petr (Journal of the science of food and agriculture, 2012)
BACKGROUND: Particle‐stabilised emulsions, so‐called Pickering emulsions, are known to possess many beneficial properties, including being extremely stable. Starch granules isolated from quinoa have been used as emulsion stabilising particles. The granules were intact, 1–3 µm in diameter and modified with octenyl succinic anhydride to increase their hydrophobicity. Starch granules, as opposed to most other particles used to generate Pickering emulsions, are edible, abundant and derived from natural sources. RESULTS: Emulsions produced by high shear homogenisation had droplet sizes of 9–70 µm depending on the starch‐to‐oil ratio. Droplet size decreased with increasing starch‐to‐oil ratio, but was unaffected by the oil phase volume over a range of 5–33% oil (v/v). Although the drops were large and subject to creaming, their size remained unchanged over a period of 7 days. By adjusting the starch‐to‐oil ratio drops could be made to be buoyancy neutral to prevent creaming. Rheological characterisation indicated a gel structure with an elastic modulus in the range 200–2000 Pa depending on droplet size. CONCLUSION: This work has demonstrated the successful use of starch granules to stabilise emulsions which may find applications beyond that of food, for example in cosmetics and pharmaceutical formulations. Copyright © 2012 Society of Chemical Industry